Ameliorate the cadmium toxicity in Solanum tuberosum L. plants with selenium and silicon application - Athos Odin Dorneles; Aline Pereira; Gessieli Possebom; Camila Tarouco; Liana Rossato; Luciane Tabaldi (Advances in Horticultural Science, 2018)
The present study aimed to prove the efficiency of Se or Si as relievers of the Cd toxicity in potato plants. Solanum tuberosum plants, Asterix genotype, from in vitro propagation were placed in pots with sand and irrigated with complete nutrient solution for 60 days under six treatments: T1: Control (nutrient solution); T2: 2.5 µM Se; T3: 2.5 mM Si; T4: 50 µM Cd; T5: 50 µM Cd + 2.5 µM Se; T6: 50µM Cd + 2.5 mM Si. The treatments were arranged in completely randomized design, with four replicates for each treatment and six plants per replicate. The plants were collected at 30 and 60 days after application of the treatments. Cadmium was highly toxic in all parameters (dry and fresh weight, plant height, leaf number, leaf area, root and photosynthetic parameters), in both assessments. However, Se and Si were effective in mitigating Cd toxicity in all parameters, although Si has been shown to be more efficient than Se in dry weight and plant height parameters. Thus, from data obtained in this study, it is clear that the beneficial elements tested have power to ameliorate Cd toxicity.